Modern views on erectile dysfunction and new methods for its treatment - A. L. Vertkin; D. Yu. Pushkar; D. Z. Dolaberidze; Yu. S. Polupanova (Кардиоваскулярная терапия и профилактика, 2005)
About 150 million men worldwide suffer from erectile dysfunction (ED). In the next 25 years, this figure could double. High ED prevalence is explained not only by ageing problems, but also by increased prevalence of diseases and taking medications, causing sexual dysfunction. Therefore, ED is not only a factor determining male quality of life, but also one of the principal social parameters of the health care system in general.